Plan estratégico de mejoramiento de procesos de producción de la empresa "Orfebrería Metálica Ambato" de naturaleza artesanal dedicada a la elaboración de altares de aluminio, ubicada en la ciudad de Ambato, provincia de Tungurahua - Silva Osorio, Danny Gabriel (2010)
Metallic goldsmith Ambato dedicated to the production and marketing of ardent chapels, which has the main probloema poor organization in the management of their processes and the objectives to be achieved with the development of the strategic plan defining the frame is also determined reference serve as a basis in the investigation and all methods and techniques necessary for the development of the thesis, besides the schedule is set to follow in the development of it.